2013
DOI: 10.1002/eji.201343577
|View full text |Cite
|
Sign up to set email alerts
|

Preserved antibody levels and loss of memory B cells against pneumococcus and tetanus after splenectomy: Tailoring better vaccination strategies

Abstract: Splenectomized patients are exposed to an increased risk of septicemia caused by encapsulated bacteria. Defense against infection is ensured by preformed serum antibodies produced by long-lived plasma cells and by memory B cells that secrete immunoglobulin in response to specific antigenic stimuli. Studying a group of asplenic individuals (57 adults and 21 children) without additional immunologic defects, we found that spleen removal does not alter serum anti-pneumococcal polysaccharide (PnPS) IgG concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 42 publications
(57 reference statements)
5
33
1
4
Order By: Relevance
“…We have shown in previous studies that splenectomy is associated with an extreme reduction of the B-cell memory pool (25,26). In contrast with these observations, in our splenectomized ITP patients, the frequency of memory B cells was in the normal range with a prevalence of switched memory B cells (Figure 4a).…”
Section: Splenectomy Does Not Influence Antibody Production In Itp Pacontrasting
confidence: 92%
See 2 more Smart Citations
“…We have shown in previous studies that splenectomy is associated with an extreme reduction of the B-cell memory pool (25,26). In contrast with these observations, in our splenectomized ITP patients, the frequency of memory B cells was in the normal range with a prevalence of switched memory B cells (Figure 4a).…”
Section: Splenectomy Does Not Influence Antibody Production In Itp Pacontrasting
confidence: 92%
“…Splenectomy is performed in ITP patients with the aim of sparing from destruction platelets tagged by autoantibodies. We have shown that the removal of the spleen causes depletion of both IgM and switched memory B cells (Figure 4a, right) (25,26,31). The reduction of IgM memory B cells remains a permanent characteristic of splenectomized individuals, whereas switched memory B cells are slowly regenerated over time (31)(32)(33).…”
Section: Articlesmentioning
confidence: 86%
See 1 more Smart Citation
“…However, various studies have shown that PPS induce efficient activation of IgM + memory B cells (IgM + IgD + CD27 + ) and generation of long-lived plasma cells (CD38 + CD20 low ). This is accompanied by the generation and persistence of IgM and IgG antibodies against PPS [101][102][103][104][105][106][107][108]. IgM + memory B cells circulating in the blood are the peripheral correlates of the marginal zone B cells of the spleen.…”
Section: Immunogenicitymentioning
confidence: 99%
“…75 For patients who receive vaccines after splenectomy, the antibody response to the immunizations should be measured to determine the need for booster doses, as studies in children with Hodgkin disease showed poor antibody response to vaccines given after splenectomy. 76 Compared with those of healthy individuals, the immune systems of patients with hyposplenia can mount only a small protective antibody response to polysaccharide antigens, which may result in vaccine failure. Therefore, conjugated vaccines are preferred in these patients.…”
Section: Special Considerations In Splenectomized Patientsmentioning
confidence: 99%